Philebus - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Philebus" by Plato is a philosophical dialogue written around 360-347 BC. It presents a debate between Socrates and two young Athenians about whether pleasure or reason constitutes the highest good. The conversation explores the nature and hierarchy of different pleasures, distinguishing between beneficial and harmful forms. Through this ethical investigation, Socrates examines broader questions of being, knowledge, and proper measure. The dialogue concludes with a universal value order that assigns pleasure its appropriate$1 (Bbut subordinate$1 (Bplace in the good life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Philebus
Socrates
Release date is 1999-05-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Pleasure -- Early works to 1800